Perancangan Untuk Menentukan Ukuran Baju Berdasarkan Postur Badan Menggunakan Metode Sistem Pakar - Manihuruk, Yohanes Septada (STMIK Budi Darma, 2019)
In globalizing world, for available sectors finding themselves a place is getting harder economically and commercially. This situation leads them to follow the latest technology to go ahead in common market. One of the latest technologies in textile field is trying on clothes for people in virtual environment. Here the biggest problem is to measuring and determining the size of the body. The aim of this study is to develop decision support system software to determine the most suitable body size. With this study, it is enabled to give easier and quicker result for the expert system.